Effect of Carbonisate Particles on the Properties of Active Carbons - Bronislaw Buczek (Adsorption Science & Technology)
In this article, the effect of particle geometry on the properties of active carbons, which are obtained by treating steam with hard coal-tar carbonisate, is reported. Different shapes of carbonisates were activated by superheated steam at 1123 K in a monolayer reactor with burn-off rates between 45.3% and 72.0%. Steam activation leads to a faster development of ring-shaped particles, and the kinetics of the process influence surface area Brunauer–Emmet–Teller, surface mesoporosity and the micropore volume. The micropore and mesopore structures of active carbons are evaluated using nitrogen adsorption/desorption isotherms and the corresponding parameters of the Dubinin–Radushkevich equation are presented. Micropore-size distribution is calculated using the Horvath–Kawazoe method. The results of these textural investigations showed that a more uniform micropore structure and better mechanical properties are present in ring-shaped active carbon particles than that were reported earlier.